Mycobacterium tuberculosis DosR Regulon Gene Rv2004c Encodes a Novel Antigen with Pro-inflammatory Functions and Potential Diagnostic Application for Detection of Latent Tuberculosis - Doddam, Sankara Narayana; Peddireddy, Vidyullatha; Ahmed, Niyaz (Frontiers in Immunology, 2017)
Abstract: Approximately 1.7 billion population of the world contain latent Mycobacterium tuberculosis (Mtb) with a substantial risk of progression to clinical outcome. Containment of seed beds of Mtb is essential to eliminate tuberculosis completely in high burden settings like India. Hence, there is an urgent need for the development of putative serological markers for detection or vaccine candidates to prevent latent tuberculosis infection (LTBI). DosR regulon antigens of Mtb might serve as attractive targets for LTBI diagnosis or vaccine development as they are specifically expressed and are up-regulated during latent phase. In this study, we investigated the role of Rv2004c, a member of DosR regulon (exclusive to Mtb complex), in host pathogen interactions and its immunogenic potential in LTBI, active TB and healthy control cohorts. Rv2004c elicited strong antibody response in individuals with LTBI compared to active TB patients and healthy cohorts. Recombinant Rv2004c induced pro-inflammatory cytokine response in human PBMCs and THP1 cells via NF-κB phosphorylation. Interaction of Rv2004c with TLR-2 was confirmed using HEK-Blue hTLR-2 and pull-down assays. Rv2004c enhanced the surface expression of TLR-2 at mRNA and protein levels in THP-1 cells. Our findings revealed that Rv2004c induces strong humoral and cell mediated immune responses and helps in adaptation to adverse granulomatous conditions that provide an intracellular survival advantage. Henceforth, we propose Rv2004c as a putative latent diagnostic marker or an attractive target for vaccine development.